Association Between Helicobacter Pylori Infection and Vitiligo - Rashid, Nazia; Rahman, Atiya (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association between Helicobacter pylori infection and vitiligo in patients visiting a tertiary care hospital of Punjab, Pakistan. Study Design: Case control study. Place and Duration of Study: Department of Dermatology, Combined Military Hospital, Lahore Pakistan, from Oct 2021 to Mar 2022. Methodology: A total of 60 adult vitiligo patients and 60 healthy controls, of both genders, were included in the study. Their ages ranged from 18-70 years. All study participants underwent stool antigen test to detect the presence of Helicobacter pylori antigen. Results: The mean age of the cases was 43.47±8.16 years whereas it was 40.08±7.42 years in the controls. The mean duration of disease was 4.133±1.21 months. H. pylori Infection was detected in 36(60%) cases as compared to 11(18.3%) controls (p<0.001, OR=6.68); which was found to be statistically significant. Conclusion: Significant association between H. pylori infection and vitiligo was demonstrated in the current study.